Gender differences in the patterns of Internet use among students : a case study of the University of Zambia - Khanal, Shrwan Kumar (2011)
The purpose of this study is to examine differences in the patterns of Internet use between male and female students at the University of Zambia. The patterns of internet use are examined in terms of the experience, frequency and the place of Internet use. The gender and technology theory has been envisaged as the basic foundation of this study. The theory claims that technologies in general are created by men and thus serve their interests at first. The study was carried out by applying a cross-sectional survey method in autumn 2007. The empirical data was collected by using a structured questionnaire and targeted at 300 randomly sampled students at the University of Zambia. The analysis is based on 215 respondents. The data consists of several questions of which nine structured questions were used in the study at hand. The first six questions are related to the personal characteristics of respondents and other three to the patterns of Internet use. The study reveals that men have longer Internet experience then women. However, Internet use experience and gender turned out to be independent variables. In the same way, men proved to be more frequent users than women. Statistical tests showed a strong association (p<0.05) between gender and the frequency of Internet use. Finally, the study found no direct association between gender and the place of Internet use. However, gender played a significant role in determining the place of Internet use when the effects of age, educational level and school factors were controlled.